Assembling the capacity to care: Caring‐with precarious housing. Issue 4 (5th April 2019) - Power, Emma R.
Abstract : In a period when care is being cast as an individual responsibility there is a need to invigorate analyses of caring capacity, of the factors and relations that make care possible. This paper develops caring‐with as an analytic to guide analyses of caring capacity. Caring‐with brings feminist care ethics together with assemblage thinking. It innovates from Tronto's identification of "caring with" as the fifth phase of care to figure care as a generative sociomaterial relation that is productive of and emergent through assemblages of actors who are not always supportive of care. Caring‐with advances three frames for conceptualising caring capacity. First, caring‐with situates care in a sociomaterial and performative frame. Second, it places care in a temporal frame, speaking to the historical and generative depth of relations that are the foundation and future of care. Third, it theorises the production and translation of care across space. These concepts are empirically examined through the caring experiences of single older women living in precarious housing in Sydney, Australia. Interviews with these women show how housing assemblages shape the emergent potential for care, co‐constituting the capacity for individuals to take part in caring practices (for self and others) and to achieve basic care needs (including needs for food, energy, and appropriate housing). Caring‐with provides a framework for conceptualising caring capacity in unequal worlds and illuminates the adaptive and creative agencies that generate and hold care together. It also points to new ways of conceptualising caring responsibility as a distributed achievement. Finally, caring‐with suggests an approach to conceptualising housing within care research. Abstract : At a time when care is being cast as an individual responsibility, this paper asks what makes care possible. It develops caring‐with as an analytic to guide analysis of caring capacity. Caring‐with brings feminist care ethics together with assemblage thinking to place care in a sociomaterial, temporal, and spatial frame. The paper theorises the production and translation of care across space and identifies the assemblages that enable future care. Empirically it asks how older women care in precarious housing.